Proportional and Accountable Justice: An Ethical-Legal Study of Exodus 21:12–14 in Responding to Contemporary Criminal Justice Issues - Ira Berkat Ampugo; Christiany Hutabarat; Octavianus Nathanael; Mulina Tarigan (International Journal of Christian Education and Philosophical Inquiry, 2026)
Contemporary criminal justice systems continue to face challenges in ensuring that law enforcement is not merely legal-formal but also proportional, accountable, and humane, particularly in distinguishing intentional from unintentional homicide. This study examines the ethical-legal principles of Exodus 21:12–14 to explore their relevance for contemporary criminal justice. Specifically, it analyzes the principle of intent in determining criminal responsibility, examines the ethical significance of sanctuary as an early form of legal protection, and critiques the misuse of religious or institutional authority as a means of avoiding legal accountability. This qualitative study employs a literature-based approach through biblical exegesis and ethical-legal analysis. The findings identify three enduring ethical principles: (1) criminal liability should be assessed based on intentionality rather than solely on the resulting act; (2) sanctuary functions as an early expression of legal protection and procedural justice for unintentional offenders; and (3) the command to remove premeditated murderers even from the altar rejects all forms of impunity and affirms equal accountability before the law. The study concludes that Exodus 21:12–14 offers enduring ethical-legal insights that enrich contemporary discourse on criminal justice by promoting proportional, accountable, humane, and impartial law enforcement.